The Diagnosis of Venous Thromboembolism - Hogg, Kerstin; Wells, Philip S.; Gandara, Esteban (Seminars in Thrombosis and Hemostasis, 2012)
Venous thromboembolism (VTE) is a serious and potentially fatal medical condition. Correct diagnosis and early treatment of VTE with anticoagulant drugs are critical steps in preventing further complications and recurrence. Evidence suggests that patients with suspected deep vein thrombosis (DVT) or pulmonary embolism (PE) should be managed with a diagnostic strategy that includes clinical pretest probability assessment, D-dimer test, and imaging. Clinical probability scoring, complemented by selective D-dimer testing, has become the recommended strategy for diagnosis. The reason is that overwhelming evidence suggests that patients with suspected VTE are better managed with a diagnostic strategy. If diagnostic algorithms are followed correctly, the chances of adverse events are extremely low (< 1%) in patients in whom VTE has been ruled out, whereas incomplete strategies leads to an increased risk of recurrent VTE or death. This review focuses on the application of diagnostic strategies with suspected DVT or PE into daily clinical practice while discussing the benefits and disadvantages of different approaches.
Keywords: pulmonary embolism; deep vein thrombosis; clinical prediction rules; D-dimer